2023
DOI: 10.3390/ijms241914888
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omic Temporal Landscape of Plasma and Synovial Fluid-Derived Extracellular Vesicles Using an Experimental Model of Equine Osteoarthritis

James R. Anderson,
Emily Johnson,
Rosalind Jenkins
et al.

Abstract: Extracellular vesicles (EVs) contribute to osteoarthritis pathogenesis through their release into joint tissues and synovial fluid. Synovial fluid-derived EVs have the potential to be direct biomarkers in the causal pathway of disease but also enable understanding of their role in disease progression. Utilizing a temporal model of osteoarthritis, we defined the changes in matched synovial fluid and plasma-derived EV small non-coding RNA and protein cargo using sequencing and mass spectrometry. Data exploration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Bioinformatics analysis was performed to analyze the biological processes and pathways affected by the DE miRNAs and their putative mRNA targets in order to enhance our understanding of the roles of the dysregulated miR-NAs in the pathogenesis of PTOA. Several plasma EV DE miRNAs identified in our study, including miR-let7, miR-29, miR-144, and miR-199, and miR-1307, were similarly altered in studies 12,13 evaluating the temporal transcriptomic profile of plasma EVs in an equine model of induced OA. Furthermore, miR-95, miR-149, miR-181, miR-193, miR-195, miR-199, and miR-411 identified in our study were recognized as miRNAs and exosomal miRNAs modified in humans with OA.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Bioinformatics analysis was performed to analyze the biological processes and pathways affected by the DE miRNAs and their putative mRNA targets in order to enhance our understanding of the roles of the dysregulated miR-NAs in the pathogenesis of PTOA. Several plasma EV DE miRNAs identified in our study, including miR-let7, miR-29, miR-144, and miR-199, and miR-1307, were similarly altered in studies 12,13 evaluating the temporal transcriptomic profile of plasma EVs in an equine model of induced OA. Furthermore, miR-95, miR-149, miR-181, miR-193, miR-195, miR-199, and miR-411 identified in our study were recognized as miRNAs and exosomal miRNAs modified in humans with OA.…”
Section: Discussionmentioning
confidence: 53%
“…Our study identified synovial fluid EV DE miR-NAs, including miR-10, miR-29, miR-34, miR-99, miR-107, miR-126, miR-144, miR-146, miR-215, and miR-486, that were also altered in studies 12,13,27 evaluating the temporal transcriptomic profile of synovial fluid EVs in an equine models of naturally occurring and induced OA. In addition, miR-21, miR-29, miR-34, miR-101, miR-105, miR-127, miR-130, miR-144, miR-146, miR-195, miR-199, miR-411, and miR-486 from our study were recognized as miRNAs and exosomal miRNAs modified in humans with OA.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In several brain diseases, including multiple sclerosis and spinal muscular atrophy, effective diseasemodifying treatments can normalize NfL levels, and reduction in NfL levels is associated with the clinical effectiveness of the treatment. 150,151 Regarding inflammatory diseases, proteomics of synovial fluid and plasma revealed that there is a mild time series pattern of expression during osteoarthritis progression as reported by Anderson et al 152 At the initial induction of osteoarthritis, there was a decrease in proteins responsible for signal transduction and regulation of signaling events at day 10, followed by an increase at day 63. On day 10, there was also an initial response in proteins that are responsible for conducting immune system responses.…”
Section: Neurodegenerative Diseases and Inflammationmentioning
confidence: 69%